An integrated mobility framework for ad hoc distributed personal networks. (5th April 2010) - Bolla, R.; Repetto, M.
Advances in wireless communications have driven an interest towards ubiquitous computing environments for nomadic users. This has led to a more user-centric vision of the network and to the concept of personal network: the user exploits his personal devices (both local and remote) and those in the surrounding environment to build dynamic ad hoc communication systems for the best experience in enjoying multimedia. In this paper, we propose a mobility framework for personal networks based on the idea of a 'personal mobile address' to bind a network address to the user rather than to a network interface, allowing the address to follow the user as he moves. We show how this mobility framework could be used for real-time interactive communications, in particular for voice-over-IP sessions managed by SIP. Moreover, we sketch a software architecture for this framework and evaluate its feasibility by means of a prototype.